2022
DOI: 10.3390/jfb13040197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effects of Various Irrigating Solutions on Chemical Structure of Root Canal Dentin Using FTIR, SEM, and EDS: An In Vitro Study

Abstract: Background: Sequential chemical application for irrigating a root canal during chemomechanical debridement can affect the dentin microstructure. Understanding the effects of various irrigants on chemical properties of dentin can elucidate their effects on physical properties and thereby explain the higher incidence of structural failure in endodontically treated teeth. This in vitro research aimed to compare and evaluate the effects of three different irrigating solutions on the chemical structure of root cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…9 Dentin samples, when irrigated with NaOCl, revealed changes in organic and mineral contents under electron-dispersive spectroscopy. 20 All these factors explain the lowest fracture resistance in the NaOCl-treated DES group. Therefore, in a clinical scenario, IES is recommended whenever it is possible.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…9 Dentin samples, when irrigated with NaOCl, revealed changes in organic and mineral contents under electron-dispersive spectroscopy. 20 All these factors explain the lowest fracture resistance in the NaOCl-treated DES group. Therefore, in a clinical scenario, IES is recommended whenever it is possible.…”
Section: Discussionmentioning
confidence: 96%
“…9 Dentin samples, when irrigated with NaOCl, revealed changes in organic and mineral contents under electron-dispersive spectroscopy. 20…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mittal et al, [ 35 ] observed that NaOCl showed the highest bacterial count reduction, followed by ozonated olive oil; the least bacterial reduction of Ozonated olive oil may be explained by the ozonolysis reaction is meaningless if peroxide released by ozonated oil could not be quantified [ 36 ]. Moreover, a study conducted by Padmakumar et al [ 37 ] had found that NaOCl substantially decreased the dentin’s organic components like carbonate and phosphate in comparison to ozonated olive oil and silver citrate as new irrigating solutions; this may be linked to the viscous nature of ozonated olive oil which restricts its penetration.…”
Section: Discussionmentioning
confidence: 99%